The role of divergent thinking in interpersonal trust during the COVID-19 pandemic: creative aspects - Palmiero, Massimiliano; Palumbo, Rocco; Ceccato, Irene; La Malva, Pasquale; Di Crosta, Adolfo; Fusi, Giulia; Crepaldi, Maura; Rusconi, Maria Luisa; Di Domenico, Alberto (Creativity Studies, 2023)
Interpersonal trust relies on positive expectations about other people. Social psychology distinguishes ingroup (individuals share social identity, e.g., family) from outgroup trust (individuals do not share social identity, e.g., strangers). We conducted an experimental study to test if divergent thinking, which relies on an inclusive processing mode, differently affected ingroup and outgroup trust during the lockdown due to the COVID-19 pandemic. A sample of 114 healthy college students, with no prior or current COVID-19 infection (mean age = 23.66, sd = 2.53, 89% women) was recruited. Interpersonal trust was measured by three ingroup and three outgroup trust items. Divergent thinking was measured by the alternative uses task, which asked to find alternative uses for common objects. Divergent thinking was scored by two independent raters in terms of fluency and quality of ideas. To control for generalized anxiety and mood states, the generalized anxiety disorder scale and the Positive and Negative Affect Schedule were administered, respectively. To control for the inclusiveness of divergent thinking performance, the alternative uses task was administered using three types of instructions. Thus, the sample was divided in three groups of 38 participants according to the divergent thinking task instructions: “be-fluent: find as many different uses for the objects”, “be-creative: find creative uses for the objects”, and “be fluent and creative: find as many different and creative uses of the objects”. The hierarchical regression analyses showed that the quality, but not the quantity of divergent thinking positively predicted only outgroup trust, whereas the mood positively predicted ingroup trust. Divergent thinking task instructions did not affect interpersonal trust. Thus, in the context of the COVID-19 pandemic, the quality of divergent thinking supports only outgroup trust based on the inclusive processing mode, meaning that people showing high ability to produce uncommon, remote and clever ideas are more inclusive and by consequence more prone to trust strangers. Limitations and implications are discussed.